Thurstonian Scaling for Sensory Discrimination Methods - Jian Bi; Carla Kuesten (Applied Sciences)
Thurstonian scaling, i.e., Thurstonian discriminal distance <semantics>δ</semantics> or <semantics>d′</semantics>, can be used as a sensory measurement index to measure and monitor food sensory difference/similarity between test and control samples due to potential food contamination. It can be obtained from any one of the sensory discrimination methods. Thurstonian scaling is theoretically independent of the methods or scales used for its estimation. This paper discusses statistical inference including estimations and tests of hypothesis for <semantics>d′</semantics>. Ten basic sensory discrimination methods including six forced-choice methods and four methods with response bias are used in this paper to estimate <semantics>d′</semantics> values and their variances. Statistical tests are conducted based on the estimated <semantics>d′</semantics> values and their variances. The statistical tests include difference testing and equivalence/similarity testing for individual <semantics>d′</semantics> values for test and control samples and for two or multiple <semantics>d′</semantics> values for test samples. The application and significance of Thurstonian scaling for sensory discrimination methods are discussed generally. R codes for estimations and tests for <semantics>d′</semantics> values are provided in the paper.